TOPICAL REVIEW: Structural control of Fe-based alloys through diffusional solid/solid phase transformations in a high magnetic field - Hideyuki Ohtsuka (Science and Technology of Advanced Materials, 2008)
A magnetic field has a remarkable influence on solid/solid phase transformations and it can be used to control the structure and function of materials during phase transformations. The effects of magnetic fields on diffusional solid/solid phase transformations, mainly from austenite to ferrite, in Fe-based alloys are reviewed. The effects of magnetic fields on the transformation temperature and phase diagram are explained thermodynamically, and the transformation behavior and transformed structures in magnetic fields are discussed.